2000
DOI: 10.1161/01.cir.102.9.1033
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chronic Treatment With the Inducible Nitric Oxide Synthase Inhibitor N -Iminoethyl- l -Lysine or With l -Arginine on Progression of Coronary and Aortic Atherosclerosis in Hypercholesterolemic Rabbits

Abstract: This is the first study showing that chronic treatment with an iNOS inhibitor, L-NIL, limits progression of preexisting atherosclerosis in hypercholesterolemic rabbits. Increased intimal collagen accumulation may participate in iNOS-induced atherosclerosis progression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 41 publications
2
35
0
Order By: Relevance
“…In contrast, midterm therapy with Los (MI 35 ϩLos [15] ) did not cause a shift in the diastolic pressurevolume curve compared with MI, attenuated the impairment of LVDP and did not modify the scar collagen content. Finally, we observed that midterm and early short-term therapy with los (MI 35 ϩ Los [15] and MI 35 ϩ Los [0][1][2][3][4] ) reduced mortality at 35 days post-MI.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…In contrast, midterm therapy with Los (MI 35 ϩLos [15] ) did not cause a shift in the diastolic pressurevolume curve compared with MI, attenuated the impairment of LVDP and did not modify the scar collagen content. Finally, we observed that midterm and early short-term therapy with los (MI 35 ϩ Los [15] and MI 35 ϩ Los [0][1][2][3][4] ) reduced mortality at 35 days post-MI.…”
Section: Discussionmentioning
confidence: 84%
“…The survival rate was significantly lower in MI 35 and MI 35 ϩ Los [0] groups (P ϭ 0.019 and P ϭ 0.004 vs. the sham group). No differences were found in the MI 35 ϩ Los [15] and MI 35 ϩ Los [0][1][2][3][4] groups. At 56 days, the survival rate was reduced in the MI 56 group (P ϭ 0.017 vs. the sham group).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated that endoglin is expressed by the aortic vessel endothelium in normo-and hypercholesterolemic mice 6,7) . Moreover, endoglin expression was also detected in human and porcine atherosclerotic lesions 3,4,8) .…”
Section: Introductionmentioning
confidence: 90%
“…The significance of ONOO − -driven modifications is underscored by the implication of both NADPH oxidase (a source of O2 •− ) [10,26,27] and eNOS (a source of • NO) [28] activities in vascular endothelial dysfunction and by the fast reaction of O2 •− and • NO to yield ONOO − .…”
Section: Introductionmentioning
confidence: 99%